Faculty's acceptance of computer based technology: cross-validation of an extended model - Tunku Ahmad, Tunku Badariah; Madarsha, Kamal Basha; Zainuddin, Ahmad Marzuki; Ismail, Nik Ahmad Hisham; Nordin, Mohamad Sahari (Australian Society for Computer in Learning in Tertiary Education, 2010)
The first aim of the present study is to validate an extended technology acceptance model (TAME) on the data derived from the faculty members of a university in an ongoing, computer mediated work setting. The study extended the original TAM model by including an intrinsic motivation component — computer self efficacy. In so doing, the study assessed the direct and indirect effects of computer self efficacy on the use of the technology, via the perceived usefulness and intention to use the technology voluntarily. The second purpose of the study is to evaluate gender and age invariants of the causal structure of TAME. This cross-validation procedure determined whether gender and age group moderated the causal structure of the model, and thus the generality of TAME. The data were collected from a self reported questionnaire administered to 731 faculty members of a public university in Malaysia.The results of structural equation modeling supported the adequacy of TAME. Although the TAME’s causal structure was applicable to both male and female staff, age group appeared to moderate the structural relationships among the constructs of interest.